THEOCRATIZATION PROJECT IN BRAZILIAN POLITICS: dangers of the attempt to institutionalize discrimination against the LGBTQIA+ population in a blatant civilizational regression (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The purpose of this article is to analyze elements and forces (non-legal) that involve the recent processing and approval of an opinion by the Social Security, Social Assistance, Childhood, Adolescence and Family Committee (CPASF) of the Chamber of Deputies, on Bill 5,167 /2009 and other attached bills, whose theme is same-sex union, which not only contravenes what was decided by the Federal Supreme Court, in the judgment of the Direct Action of Unconstitutionality (ADI) 4277 and the Claim of Non-compliance with a Fundamental Precept (ADPF) 132 12 years ago; but, in addition, it demonstrates the dangerous attempt to legally impose fundamentalist and discriminatory religious agendas against the LGBTQIA+ population, disseminated through the “theology of domination” - frank supporters of the Brazilian extreme right - contrary to the democratic pillars and human dignity established with the Constitution of the Republic of 1988.